2024
DOI: 10.1029/2023gl106049
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Interpretability of Outer Radiation Belt Enhancement and Depletion Events

Donglai Ma,
Jacob Bortnik,
Qianli Ma
et al.

Abstract: We investigate the response of outer radiation belt electron fluxes to different solar wind and geomagnetic indices using an interpretable machine learning method. We reconstruct the electron flux variation during 19 enhancement and 7 depletion events and demonstrate the feature attribution analysis called SHAP (SHapley Additive exPlanations) on the superposed epoch results for the first time. We find that the intensity and duration of the substorm sequence following an initial dropout determine the overall en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…where f is the phase space density (PSD), t is the time, and S(α eq ) represents the bounce period approximated by S(α eq ) = 1.38 0.32 sin(α eq ) 0.32 ̅̅̅̅̅̅̅ ̅ sin √ (α eq ) (Lenchek et al, 1961). The lower energy boundary is set as the electron PSD at 235 keV provided by our ML model (D. Ma et al, 2022), which is primarily driven by the AL index during the post-storm period (D. Ma et al, , 2024, as shown in the solid line in Figure 1e. The lower boundary is set to be higher than in previous simulations as we focus on the relativistic electrons.…”
Section: Events Selection and Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…where f is the phase space density (PSD), t is the time, and S(α eq ) represents the bounce period approximated by S(α eq ) = 1.38 0.32 sin(α eq ) 0.32 ̅̅̅̅̅̅̅ ̅ sin √ (α eq ) (Lenchek et al, 1961). The lower energy boundary is set as the electron PSD at 235 keV provided by our ML model (D. Ma et al, 2022), which is primarily driven by the AL index during the post-storm period (D. Ma et al, , 2024, as shown in the solid line in Figure 1e. The lower boundary is set to be higher than in previous simulations as we focus on the relativistic electrons.…”
Section: Events Selection and Simulation Methodologymentioning
confidence: 99%
“…Hua, Bortnik, Chu, et al (2022), andHua et al (2023) show the maximum electron flux at different energy levels is strongly correlated to the cumulative effects of substorms instead of storms. Our previous ML models were driven only by geomagnetic indices and solar wind parameters, and with interpretable ML methods, we automatically discovered the integrated AL is a key parameter in the acceleration mechanism for relativistic and sub-relativistic electrons (D. Ma et al, , 2024. These studies indicate that we can use the AL index to model the time-varying physical parameters needed for traditional Fokker-Planck simulations, thereby obtaining a general model driven by the auroral index.…”
Section: Introductionmentioning
confidence: 96%
“…Although these studies, based on traditional statistical analysis of satellite data, have comprehensively analyzed the dependence of dropouts on various driving factors, the traditional way has important limitations in that it is difficult to isolate the impact of different driving factors. These different driving factors are intrinsically correlated with each other in a nonlinear way and may nonlinearly interact with each other to produce different effects at different locations and phases of the storm (Ma et al, 2024). The dominant driving factors and physical mechanisms that cause dropouts are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Since these nonlinearly correlated driving factors and their nonlinear interactions produce dropouts, to unravel these nonlinear correlations between various driving factors and dropouts, we take advantage of machine-learning techniques that can associate inputs with outputs in a nonlinear way, which have been widely used in space weather modeling and forecasting (Bortnik et al, 2016(Bortnik et al, , 2018Chu et al, 2017;Ma et al, 2022;Wing et al, 2022), and in discovering the important underlying/missing physical processes (Camporeale et al, 2022;Ma et al, 2023Ma et al, , 2024. In this letter, we employ Support Vector Machines (SVMs) to construct storm-time electron dropout prediction models over L = 4.0-6.0 using dropout data set based on 5-year Van Allen Probes observations from our previous study (Hua et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we adopt a state-of-the-art feature attribution method, Deep SHapley Additive exPlanations (Deep SHAP) (Lundberg & Lee, 2017;D. Ma et al, 2023D. Ma et al, , 2024, to quantify the contributions of each solar wind parameter to prediction results of the PGREFM.…”
Section: Introductionmentioning
confidence: 99%